Relationship between perceptions of fitness facility service quality and future intentions of fitness center users in Thailand - Yusof, Aminuddin; Popa, Arporn; Soh, Kim Geok (Human Resource Management Academic Research Society, 2018)
The purpose of this research was to examine the relationship between perceptions of fitness facility service quality and future intention to use campus fitness center at Mahasarakham university, Thailand. A total of 250 campus recreation fitness center users (males = 189, females = 61) comprising of students and staff from Mahasarakham University was selected to participate as subjects in the study. The questionnaire consisted of items based on the Likert-scale Service Quality Assessment Scale (SQAS) developed by Lam, Zhang and Jensen (2005). Future intention was measured using two items by Zeithaml et al. (1996): word-of-mouth communications and repurchase intentions. The results showed fitness facility service quality (ß = .300, p < .05) and overall facility service quality (ß = .278, p <. 05) contribute significantly towards predicting behavioral intention. This means fitness center users in Mahasarakham University are more likely to renew their membership and recommend the recreation center to other people if they are satisfied with the fitness facility service quality aspects.